The art of immersion with smell and sensorial theatre language - Jenič, Barbara Pia (Amfiteater (Ljubljana), 2021)
In recent decades, the trend or the need for an experience of the effect of immersion into theatre events, other branches of art, tourism, everyday business and private life has become quite evident. We are used to audio-visual communication, which, from the Renaissance onwards, became the dominant channel for delivering messages, while other senses became less important. Until the middle of the 20th century, the role of smell in theatre practices was neglected, and more important senses took over the place of communication and staging. Rarely it was used as a direct prop, but always very carefully, because, according to many experts, it cannot be controlled like sound and light. However, we have forgotten that the smell, especially in combination with the sound, can have a strong emotional impact on a spectator. Like the other senses, the scent recreates the context of memories and can evoke an intense reliving of emotions and events. It can also provoke an evaluation or re-evaluation of the past, thereby affecting the perception of the present. Reality is perceived through the adaptation of sensory information, which is shaped and interpreted under the influence of past experiences. Experiences create expectations, and expectations create our subjective reality considering everyday life and theatrical performance. This relationship is especially noticeable in sensorial theatre. In the last decade, an effort has been made to bring scents and other tools of sensorial theatre back to the stage, just as – according to foreign sources – they were an important part of events in antiquity. In this way, the stage can be enriched with an additional dimension of communication and expression. The paper presents various methods and experiments on the use of scent and other tools of sensorial theatre, evaluating their phenomenology and effectiveness from the perspective of the performing arts and psychological science.
Keywords: memories; perception of reality; psihološka potopitev; psychological immersion; sensorial theatre; senzorialno gledališče; smell; spomini; vonj; zaznavanje resničnosti